Constituting democracy law, globalism and South Africa's political reconstruction. - Klug, Heinz (Cambridge Studies in Law and Society, 2000)
Against the backdrop of South Africa's transition from apartheid, this provocative book explores the role of late twentieth-century constitutionalism in facilitating political change. While using South Africa as a case study, Klug's larger project is to investigate why there has been renewed faith in justiciable constitutions and democratic constitutionalism, despite their many flaws. This examination of South Africa's constitution-making process provides important new insights into the role of law in the transition to democracy.